Financial education in high school: An analysis of didactic activities related to uniform periodic series from the point of view of critical mathematics education - Hartmann, Andrei Luís Berres [UNESP]; De Cássia Pistóia Mariani, Rita; Maltempi, Marcus Vinicius [UNESP] (FapUNIFESP (SciELO), 2021)
The objective of this study was to identify and analyze didactic activities developed in High School which may involve decision making in economic-financial situations related to uniform periodic series. Perspectives related to Financial Education, School Financial Education, and Critical Mathematical Education provided theoretical support for the study. As this is a qualitative research in which a bibliographic survey was carried out based on Capes' Theses and Dissertations Catalog, data production also considered the principles of content analysis. Through this platform it was possible to identify 333 master's or doctorate productions, using the keyword Financial Education. After data were restricted, we selected six didactic research activities carried out in the professional modality and which developed these issues with high school students. For the analysis of activities, three descriptors were systematized, based on the studies by Muniz (2016) and Rocha (2017): Context Interpretation (D1), Decision Making (D2), and Argument in Decision Making (D3). For the activities considered, it can be highlighted that the research allowed its participants to reflect on everyday situations (identification of D1 in five activities), but the issues did not admit decision making based on the three arguments considered: Sociocultural (SC), economic-financial (EF), and behavioral (C). Therefore, it is proposed that the study of geometric progressions, strongly related to uniform periodic series, be conducted based on Financial Education and Critical Mathematical Education, still in High School.
Educação Financeira no Ensino Médio: Uma análise de atividades didáticas relacionadas a séries periódicas uniformes sob o ponto de vista da Educação Matemática Crítica
Keywords: Bibliographic Survey; Critical Mathematics Education; Decision Making; Financial Education; Geometric Progression